Present status of acid mine drainage in caol mines of secl and its prevention - Pandey, Manoj Kumar; Pradhan, Manoj; Pandey, Piyushkant (Recent Research in Science and Technology, 2014)
Acid Mine Drainage (AMD) is a very common environmental pollution problem which occurs worldwide in mining region. AMD forms when sulfide minerals in rocks are exposed to oxidizing condition in coal and metal mining, highway construction and other large scale excavations.. During mining, the exposed wall rocks come in contact with the oxygenated water, interaction between these causes generation of AMD. Bacterial activity also plays an important role in acid formation. Coal has a crucial role in meeting current needs and is a resource bridge to meet future goals. Through the enhancement of knowledge and technology the challenge is to apply the right technology in the most efficient and environment friendly way. The biggest environmental challenge facing the coal industry is the issue of greenhouse gases and acid rain. The aim of this project is to investigate the water quality parameter in relation to acid mine drainage for the Indian coal fields that includes possibilities for control, minimization and optimal feasibility for the implementation of control method. In Chhattisgarh region S.E.C.L., division of CIL plays a major role for coal extraction.The AMD management practices followed by SECL were not found adequate owing to the technological, environment and natural water resource management problems. Thus there is an urgent need of research regarding control and abatement of AMD. Depending upon site characteristics, so improved reliability and efficiency is required. An attempt is made to view the status of acid mine drainage in Indian coal mine and to study about its preventive measures is an issue of further research.